Pendampingan Budidaya Padi Gogo Beras Merah Pada Lahan Pekarangan Di Desa Aek Nabara - Samsinar Harahap; Elda Sari Siregar; Eka Nurwani Ritongan; Erti Kumala Indah; Amir Mahmud (Jurnal Transformasi Pendidikan Indonesia, 2025)
The community partnership program in the form of assistance in cultivating red rice on yard land was implemented in Aek Nabara Village, West Angkola District, South Tapanuli Regency. The Martunas Farmer Group needs assistance due to limited knowledge about the use of yard land and the cultivation of red rice. This program aims to provide knowledge on how to cultivate red rice on yard land and encourage and foster community interest in cultivating red rice. The method used is Pre-implementation, in the form of socialization, counseling and training, implementation, and Post-implementation. The results of this activity showed that the farmer group has an interest in cultivating red rice on yard land, so that it can provide additional daily needs. This activity also makes training activities and facilities more dynamic, the community is more active in learning and can be applied properly and correctly, which can be done in farmer’s yard land.Keywords : Dryland Rice, Yard Land